Biotechnological insights into the antimicrobial properties of Azadirachta indica - Parvati Yadav (Innovations in Pharmacy Planet, 2024)
Azadirachta indica, commonly known as neem, is a tropical evergreen tree renowned for its diverse antimicrobial properties. With a rich phytochemical profile, including compounds such as azadirachtin, nimbin, and terpenoids, neem has been traditionally utilized in treating various infections and inflammatory conditions. Its bioactive compounds exhibit potent antibacterial, antifungal, antiviral, and anti-inflammatory effects, making neem a promising alternative to conventional pharmaceuticals. This review explores the antimicrobial mechanisms of neem, including disruption of bacterial cell walls, membrane integrity alteration, and inhibition of biofilm formation. Advances in biotechnology, including genomic studies, metabolomics, and molecular cloning, have enhanced our understanding of neem’s therapeutic potential and facilitated the development of more effective applications. Neem’s role in modern medicine spans pharmaceutical formulations, agricultural biopesticides, and food preservation. However, challenges such as large-scale production and microbial resistance remain. Future research should focus on overcoming these challenges, optimizing extraction processes, and utilizing biotechnological innovations to enhance neem’s efficacy in clinical and industrial applications.